2007
DOI: 10.1089/lap.2006.0540
|View full text |Cite
|
Sign up to set email alerts
|

Complete Videoendoscopic Harvest And Transposition of Latissimus Dorsi Muscle for The Treatment of Poland Syndrome: A First Report

Abstract: Poland syndrome is a rare congenital anomaly characterized by unilateral chest wall hypoplasia and ipsilateral hand abnormalities. The indications for chest and breast reconstruction are determined on the basis of functional and aesthetic concerns. The traditional open approach uses a latissimus dorsi muscle flap to attain chest symmetry. Endoscopically assisted latissimus dorsi muscle harvesting has been reported previously, combined with an additional incision for muscle fixation. We present a case series us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Most patients who had an EALDF for Poland syndrome had an ‘excellent’ cosmetic result 25,28,29,33 . Using the Breast‐Q, the scores for ‘psychosocial well‐being’ and ‘satisfaction’ improved from 47.8 to 63.7 and from 23.1 to 61.7, respectively 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients who had an EALDF for Poland syndrome had an ‘excellent’ cosmetic result 25,28,29,33 . Using the Breast‐Q, the scores for ‘psychosocial well‐being’ and ‘satisfaction’ improved from 47.8 to 63.7 and from 23.1 to 61.7, respectively 25 .…”
Section: Resultsmentioning
confidence: 99%
“…8,25 Several studies have reported different approaches to improve the surgical field for an EALDF like the balloon technique 48,49 and gasless or insufflation technique with multiple trocars and laparoscopic instruments, all requiring three to four incisions. 11,23,28,29,31,36,37 In this setting, this may compromise the advantage of the endoscopic technique to reduce scarring. 25 Other authors have been able to harvest the LDF using single-port access, either with laparoscopic or robotic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 6 patients, we performed minimally invasive harvesting of the latissimus dorsi muscle flaps. The last case, we believe, is the first report of a completely minimally invasive harvest and transposition [12]. The graft was sutured subcutaneoscopically.…”
Section: Poland Syndromementioning
confidence: 89%
“…The latissimus dorsi flap generated through the endosco pic route enables the most accurate visualization and mo bilization of the vascular pedicle, as well as faster postoperative recovery 1,5,8,9 . The surgery is performed with a lateral incision or with multiple, typically 3, orifices for instruments usage.…”
Section: Discussionmentioning
confidence: 99%